Smart-dose microboost: micronutrient in order to enhance chili growth and yield in tropical farming systems: Smart-dose microboost: mikronutrien untuk meningkatkan pertumbuhan dan hasil cabai pada sistem pertanian tropis - Mulyani, Oviyanti; Sudirja, Rija; Susanto, Agus; sutari, Wawan (Jurnal AGRO, 2025)
Despite the fact that micronutrients are crucial for the growth, metabolism, and crop yield of plants, they are required in relatively small proportions. The recent advancements in agriculture have resulted in the development of biostimulant products that are abundant in micronutrients which is advantageous. The objective of this investigation was to evaluate the potential of micronutrient-enriched biostimulants (MB) to enhance the quality characteristics of chili fruits. This study was conducted at Jatinangor, West Java. The experimental plots were laid out in a Randomized Block Design (RBD) with seven treatments and repeated four times, so the total number of treatments was 28 units. The treatments consist of farmer practice and doses of 0.75; 1.0; 1.5; 2.0; 2.5 and 3.0 L ha-1 MB. The results of this experiment indicated that the treatments with doses of 2.0–3.0 L ha-1 were consistently preferable in terms of fruit quality, yield, and growth. Plants that were more productive, capable of grading fruit, and had a slightly extended shelf life after harvest were the final result of the biostimulant product, which contained micronutrients. The farmer's practice consistently failed to meet the standards of all the treated sites. The combination of biostimulants and micronutrients significantly enhanced the physiological and reproductive functions of chilies. ABSTRAK Mikronutrien, meskipun dibutuhkan dalam jumlah yang kecil daripada makronutrien, penting untuk perkembangan tanaman, fungsi metabolisme, dan produktivitas tanaman. Perkembangan terkini dalam bidang pertanian telah menghasilkan produk biostimulan yang kaya akan mikronutrien yang sangat penting. Tujuan dari penelitian ini adalah untuk menilai potensi biostimulan yang diperkaya mikronutrien (MB) dalam meningkatkan kualitas buah cabai. Panelitian ini dilakukan di Jatinangor Sumedang, Jawa Barat. Plot percobaan disusun dalam Rancangan Acak kelompok (RAK) dengan tujuh perlakuan dan diulang empat kali, sehingga total perlakuan adalah 28 unit. Perlakuan tersebut terdiri dari metode konvensional; dosis biostimulan yang diperkaya mikronutrien (0,75; 1,0; 1.5; 2,0; 2,5 and 3,0 L ha-1 MB). Hasil percobaan ini menunjukkan bahwa perlakuan dengan dosis 2,0–3,0 L ha-1 adalah yang paling konsisten unggul di seluruh parameter pertumbuhan, hasil dan kualitas buah. Produk biostimulan dengan tambahan mikronutrien membuat tanaman lebih kuat, lebih produktif, lebih baik dalam kualitas buah, dan memperpanjang masa simpan setelah panen. Dibandingkan dengan semua yang diberi perlakuan pupuk mikronutrien dan biostimulan, perlakuan konvensional memberikan respon yang paling kecil. Secara umum, penambahan mikronutrien dan biostimulan secara bersamaan dapat memberikan dampak besar pada peningkatan fungsi fisiologis dan reproduksi tanaman cabai.   Kata kunci: Biostimulan, Cabai, Keberlanjutan, Produktivitas